VIRUSES AND THEIR IMPACT ON LIVING ORGANISMS - Jiyanmuradova Shakhlo Khamdamovna; Jasurova Sabrina Jasurovna (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Annotation. Viruses are acellular forms of life that represent autonomous genetic structures. Viruses can cause harm not only to nearly all representatives of flora and fauna but also to microorganisms. The effectiveness of combating many viruses does not always yield positive results, as viruses not only have natural reservoirs in the environment but also constantly undergo mutations; therefore, the effectiveness of vaccine prophylaxis is reduced. One of the most striking examples is the long-term ineffective struggle against the human immunodeficiency virus. A particular threat to humanity is the coronavirus COVID-19, which can lead to severe complications and even death.